Коктебель как этнокультурный ландшафт Крыма - Дроздов, А.В. (Культура народов Причерноморья, 2014)
В статье раскрывается исключительная роль этнокультурного ландшафта в становлении
современного поселка Коктебель. На основе культурно-ландшафтного подхода проанализированы
известные исследования культурологических, этнографических концепций и разработки в области
этнокультурного ландшафтоведения. Для выявления положительных и отрицательных факторов
воздействия этнических общностей на природу показаны условия становления этнокультурного
ландшафта и факторы развития «экологии культуры» Коктебеля в процессе хранения и передачи
информации. У статті розкривається виняткова роль етнокультурного ландшафту в становленні
сучасного селища Коктебель. На основі культурно-ландшафтного підходу проаналізовані відомі
дослідження культурологічних, етнографічних концепцій і розробки в галузі етнокультурного
ландшафтвоведенія. Для виявлення позитивних і негативних факторів впливу етнічних спільнот на
природу показані умови становлення етнокультурного ландшафту та фактори розвитку «екології
культури» Коктебеля в процесі зберігання і передачі інформації. The article reveals the exclusive role of ethnic and cultural landscape in the development of modern
Koktebel. On the basis of cultural landscape approach known study analyzed cultural, ethnographic concepts
and developments in the field of ethno-cultural landscape management. In order to identify the positive and
negative impacts on the nature of ethnic communities shows conditions of formation of ethnic and cultural
landscape and the factors of development of the "ecology of culture" Koktebel during storage and transmission
of information.
These studies make it possible to implement the principles of historical study of modern cultural landscape,
contribute to the definition of relict cultural elements of the region is the basis for the identification and
protection of areas of cultural and natural heritage.
Information base is: ethnographic research, economy and culture of Koktebel statistical data, archival
materials, as well as the results of our study of traditional culture Koktebel.